2016
DOI: 10.17795/nmsjournal26920
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Practical Learning in the Field: A Qualitative Study of Iranian Nursing Students’ Experiences

Abstract: BackgroundClinical training is an integral part of nursing education; however, some studies have shown that it is not always efficient.ObjectivesThis study aimed to find out the factors that can impede nursing students’ clinical learning.Materials and MethodsIn this qualitative study, data were collected via reflective journal writing. Purposeful sampling was used, and 12 senior nursing students were recruited to the study. The data were analyzed using a content analysis method.ResultsThree main categories wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…This means there is a theorypractice gap in the clinical setting, and this hindered students' clinical learning. This is agreed with Jahanpouret al (32) who found that competence of clinical nurse educators and the theory-practice gap were among the most important factors affecting students' learning in clinical settings. Moreover Al Mutair (16) considered growth in applying the theoretical knowledge and skills in the clinical setting is a major task for clinical nurse teacher.…”
Section: Resultssupporting
confidence: 91%
“…This means there is a theorypractice gap in the clinical setting, and this hindered students' clinical learning. This is agreed with Jahanpouret al (32) who found that competence of clinical nurse educators and the theory-practice gap were among the most important factors affecting students' learning in clinical settings. Moreover Al Mutair (16) considered growth in applying the theoretical knowledge and skills in the clinical setting is a major task for clinical nurse teacher.…”
Section: Resultssupporting
confidence: 91%
“…Scientific writing demands keen interest, learning, and practices to disseminate research work. Nevertheless, health sciences researchers find impedance in publishing scientific work [6][7][8][9]. Medical professionals' limited reading and writing practices hurdle good scientific journals [10] and cause an under-representation of health status from developing countries [11].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Setting the conditions for optimal student nurse clinical practice, however, remains challenging worldwide. Issues reported in the literature include: lack of close supervision of students by clinical staff due to nursing shortages and inadequate collaboration between clinical staff and academia; [2] inadequate or scarce clinical placement sites, often as a consequence of increased numbers of students; [3,4] reduction in traditional clinical placement opportunities related to health system changes; [4] competition with other health disciplines for the same practice settings; [2][3][4] shortages of academically qualified faculty members; [2,5,6] and, academic expectations that influence faculty workloads and make it difficult to hire and retain faculty with current clinical expertise or for faculty members to maintain their clinical expertise. [5][6][7] Such issues are common globally but gain in intensity in more resourceconstrained national contexts such as Ghana.…”
Section: Introductionmentioning
confidence: 99%